Wood Micro-structural Studies of Indian Rutaceae Part III : Tribe Flindersiae - Bhardwaj, Nisha; Gupta, Sangeeta (Indian Forester, 2009)
The present study deals with the detailed wood anatomy of the Indian species of the genus Chloroxylon swietenia DC belonging to the tribe of Flindersioideae of the family Rutaceae. Photomicrographs have been given for the diagnostic features. The wood of this tribe is used for carving, turnery and mathematical instruments. The genera includes mostly diffuse porous woods with marginal and diffuse parenchyma; exclusively simple perforation plate; nonvestured, alternate and minute inter vessel pitting with coalescent aperture. In all the samples prismatic crystals in chambered parenchyma cells were observed. New reports include coalescent aperture in the vessels and crystals in fibres for the first time.